Frome Image Building to Discrediting Political Opponents. Hate Speech as a Strategy in Press Releases (Hassrede – ein multidimensionales Phänomen im interdisziplinären Vergleich, 2020)
The subject of these considerations is hate speech in press releases of political parties as a strategy to discredit political opponents. The article published on the official website of the Alternative for Germany (AfD) contained terms such as the red show of misfits (social democrats) or sadistic domino (Angela Merkel) in relation to competing groups and politicians. The question arises as to the purpose of using such elements in types of texts whose primary function is to transmit information in a positive way and as a result relay the writer’s optimism. The paper shall start from the presentation of specific features of press releases; furthermore, an attempt will be made to determine its function in the field of political communication from the point of view of political text typology and genres. Throughout the rest of the paper quantitative analysis of selected materials will be presented, including sixty press releases of the Alternative for Germany party and a qualitative analysis of one selected text will be conducted. Special emphasis will be put on the pragmatic, semantic, grammatical and rhetorical levels of hate speech.